Respuesta :
For this case we have a function of the form:
y = A * (b) ^ t
Where,
A: initial amount
b: growth rate
t: time
Substituting values we have:
y = 1000 * (3) ^ ((1/8) * t)
For 24 years we have:
y = 1000 * (3) ^ ((1/8) * 24)
y = 27000
Answer:
D) 27,000; exponential
y = A * (b) ^ t
Where,
A: initial amount
b: growth rate
t: time
Substituting values we have:
y = 1000 * (3) ^ ((1/8) * t)
For 24 years we have:
y = 1000 * (3) ^ ((1/8) * 24)
y = 27000
Answer:
D) 27,000; exponential
Answer:
D ) 27,000; exponential
Step-by-step explanation:
y = A(b) ^ t
A: initial amount
b: growth rate
t: time y = 1000 * (3) ^ ((1/8) * t)
For 24 years we have: y = 1000 * (3) ^ ((1/8) * 24) y = 27000